MENINGKATKAN MINAT BELAJAR SISWA MENGGUNAKAN MEDIA WORDWALL PADA MATA PELAJARAN IPA DI KELAS IX MTSN 2 BUNGO - Islamiyah , Suci; Baili; Dewi, Yurnalisma; Puji Lestari, Dyah; Mulya , Putri; Rohmah, Aspiatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ learning interest in Science subjects through the use of Wordwall media in class IX of MTs Negeri 2 Bungo. The research method used was Classroom Action Research (CAR) employing the Kemmis and Taggart model, which consists of four stages: planning, implementation, observation, and reflection. The research was conducted in two cycles, each consisting of one meeting. The subjects of this study were students of class IX D at MTs Negeri 2 Bungo. Data were collected through observation, student learning interest questionnaires, and documentation, then analyzed using descriptive qualitative and quantitative techniques. The results showed that the use of Wordwall media was effective in increasing students’ learning interest in the topic Human Coordination System: Nervous System. In the first cycle, students began to show curiosity and engagement in the learning process, although there were still some obstacles such as limited media access and uneven student participation. Improvements were made in the second cycle by adding a projector, introducing more varied games, and providing rewards, which resulted in a significant increase in students’ learning interest. Students became more active, enthusiastic, and motivated during the learning process. Thus, the application of Wordwall media proved effective in enhancing students’ learning interest in Science and can serve as an interactive and engaging learning alternative in madrasah settings..